Relationship between Post-Divorce Parental Alienation and Adolescents’ Meaning in Selected High Schools in Kiambu County, Kenya - Wanjao, Jane Njango; Njoroge, Margaret W; Kamau, Elizabeth (THE INTERNATIONAL JOURNAL OF HUMANITIES & SOCIAL STUDIES, 2023)
Recent evidence stipulates that various parental contributions, such as parental warmth, empathetic parenting, encouragement, and parental involvement in general, are positively associated with adolescent flourishing. In this regard, post-divorce parental alienation creates an unfavourable environment that may disorganize adolescents from adaptive living. The purpose of the study was to examine the relationship between post-divorce parental alienation and adolescents' meaning/purpose in selected high schools in Kiambu County, Kenya. The study was anchored on PERMA well-being theory. The study employed a descriptive survey design using a mixed methods approach. Multistage sampling, inclusion, and exclusion criteria aided by cluster sampling were used to select 240 adolescents from a population of 3776. Purposive sampling was employed in the selection of 32 respondents in the FGD. Qualitative data were collected via audio-tapes recordings and field notes. Verbatim data were transcribed. Quantitative data were collected using Baker strategy questionnaire (BSQ) and the PERMA-Profiler. Descriptive statistics included frequencies, and percentages, while Chi-square analysis was used to test for the hypotheses. The computer software SPSS version 25 aided in the analysis. The findings revealed that post-divorce parental alienation affects adolescents’ meaning /purpose. The study recommends that intervention measures be implemented in consideration of factors as follows. The implications of this research suggest the need for Family lawyers working with children of a divorced parents to carry out thorough investigations before awarding child custody to parents. Marriage and family therapists working with children of divorced families could profit from these results, which clearly show the negative effects of PA on adolescents' well-being. The study suggests that these professionals use the findings of the study to understand commonly employed PA tactics and how they affect those alienated in order to help them cope. Further, the study suggests these professionals use the BSQ to assess PA in this population.
Keywords: Post-divorce; parental alienation; adolescents; meaning